Ideas about the stressfulness of the parental role in potential parents: objective and subjective determinants - I. V. Tikhonova; N. S. Shipova; Yu. V. Misiyuk (Acta Biomedica Scientifica, 2024)
Studying stress factors of childbirth intentions is an important parameter in population development policy making. There is no data on the comparison of the relative importance of different types of determinants and stress inducing factors of parenting in the scientific literature.The aim. To study the factors determining the ideas about the stressfulness of the parental role among modern youth.Methods. The  sample consisted of  364  students with no  parenting experience. Three groups were identified, differing in their orientation towards having children: a group with a focus on single-child parenting (257 people); group with childfree focus (32 people); group with a focus on multi-child parenting (75 people). The following methods were used: socio-demographic questionnaire; “Parental Stress Scale” (J.O. Berry, W. Jones, 1995; adapted by Yu.V. Misiyuk, I.V. Tikhonova, 2022); “Intensive Parenting Attitudes Questionnaire (M. Liss, H.H. Schiffrin, V.H. Mackintosh, H. Miles-McLean, M.J. Erchull, 2013; adapted by Yu.V. Misiyuk, 2022); express version of the “World Assumptions Scale” (R. Yanoff-Bulman; modified by M.A. Padun, A.V. Kotelnikova; author’s semi-structured interview.Results. We  analyzed the  ideas about  the  stress that  is  associated with fulfilling the  parental role. Parameters that potentially act as  the  factors determining the stressfulness of parenthood are considered. The specificity of ideas on parental stress and its determinants is analyzed in accordance with the dominant orientation towards childbearing.Conclusion. Ideas about the stressfulness of the parental role are determined by objective (age, status of personal relationships, education) and subjective (assessment of family relationship, attitudes towards the need to stimulate the child’s development, essentialism and  satisfaction from  raising children) factors, but  subjective ones have the greatest weight. The specificity of the determination of ideas about parental stress depending on the orientation towards childbearing has been revealed.